The Context of Woman’s Clothes Verses and It’s Influence on the Concept of Woman’s Dressing (A Comparison of Four Indonesian Exegeses) - Tri Hermawan (Millati: Journal of Islamic Studies and Humanities, 2017)
This paper will compare the commentaries of the verses which tell about women's dressing, where the explanation focuses on four Indonesian quranic commentaries made at different times; the classical dan medieval period. The four books are Turjuman al-Mustafid Interpretation, Qur'anul Karim Interpretation, Al-Nur Interpretation, and Al-Misbah Interpretation. This study is a qualitative research in which the data taken in this study are derived from some literatures or books. The results of the study reveal that the differences of commentaries are; Turjuman al-Mustafid regulated women to cover their whole body except face and palms, Quranul Karim required women not to be look like wanton women,  Al-Nur told women to cover up their body and to wear a scarf on the head, while Al Misbah asked women to dress in a respectable manner (though not wearing jilbab). These differences are caused by the differences in the time of writing, the background of the life of commentators and the books used as references in commenting the verse.